Relationship between body condition and level of parasite infestation in grazing cattle as a criterion for selective deworming - Morales, Gustavo (2012)
The aim of this study was to evaluate the relationship between the level of Strongyletype parasite infestation and body condition in Criollo Rio Limon (n=42), Bos taurus (n=54) and Bos indicus (n=11). The cattle belonged to two farms at Pedraza municipality in Barinas State (Venezuela). Fecal samples were analyzed by the quantitative McMaster technique using saturated saline solution. Body condition score (BCS) was evaluated using a scale of 1 to 5 (1 = thin, 5 = obese) where 2.5 was the cut-off point. The animals were classified as resilient (BCS>2.5 and high egg counts per gram of feces [>800]), resistant (BCS>2.5 and null, mild or moderate parasite burden), sensitive (BCS<2.5, high parasite burden), and false parasite problem (BCS<2.5 and low or no parasite burden). The Criollo Río Limón was associated with resilient and resistant categories, the Bos taurus to the sensitive and false parasite problem categories, and Bos indicus to the resistant category. The relationship between body condition and level of Strongyle-type parasite infestation allows an efficient and rapid identification of the fraction of cattle requiring treatment with anthelmintics.